Validation of RP-HPLC Method for Determination of Curcumin Content Obtained from E-Commerce - Dwi Framono, Indra; Hardani, Prisma Trida; Purbosari, Ira (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Among the curcuminoid compounds, curcumin is the dominant component and has promising hepatoprotective activity. Although the curcumin content in turmeric rhizomes varies, it is not less than 3.82%. The pharmacological effectiveness of curcumin is highly dependent on accurate and consistent dosage. Along with the rise of traditional medicine sales through e-commerce, determining curcumin levels is crucial to ensure product safety, efficacy, and quality. This study aims to measure the curcumin content in turmeric capsules obtained from e-commerce using the reversed-phase HPLC method with octadecylsilane stationary phase (C18), mobile phase HPLC grade methanol: 0.5% phosphoric acid (60:40), flow rate 0.8 ml/min with a wavelength of 425 nm. The validation parameters tested were selectivity, linearity, accuracy, precision, LOD and LOQ. The results showed that the reversed phase HPLC method has good selectivity with the same Rt value 2.624 and Rs ≥ 1.5 on curcumin standard obtained RS of 1.70 and 1.88 on the sample. The linearity test results obtained an R value of 0.9999 means that it meets the requirements of R > 0.99. The accuracy test with 80% addition is 96.141% ± 0.682, 100% addition is 94.081% ± 5.789 and 120% addition is 94.591% ± 5.723. In the repeatability test % RSD values obtained were 0.789%, 6.153%, and 5.500% respectively, which means that the %RSD < 8% is qualified. In the LOD and LOQ results obtained 0.917 µg/mL and 3.058 µg/mL. Validation of analytical methods in accordance with established requirements. The curcumin content produced in samples that have a BPOM license is higher at 12.757% ± 0.7177 than those that do not have a BPOM license which is 0.187633% ± 0.00583.